Church and settler in colonial Zimbabwe : a study in the history of the Anglican Diocese of Mashonaland/Southern Rhodesia, 1890-1925 - Welch, Pamela. (Studies of Religion in Africa, 2008)
This book examines the history of the Anglican Diocese of Mashonaland/Southern Rhodesia (virtually co-extensive with modern Zimbabwe) in the period 1890-1925, when its institutions took shape and its religious character was formed. While work among indigenous communities is outlined, the primary subject is the church's work with white settlers. A fresh general narrative is provided and an examination of clergy recruitment and finance relates events in Mashonaland to developments in global Anglicanism. Among the questions addressed are those of religion and empire, church and state and the complexities of relationship between the Church of England and her overseas extensions, particularly those covering areas of white settlement. Local developments in religious practice are also explored: most striking of these was the settler apprehension of the vast landscapes of South-Central Africa as a locus of the sacred and their custom of veld burial.